2001
DOI: 10.1081/css-120001103
|View full text |Cite
|
Sign up to set email alerts
|

Methods for evaluation of easily-reducible iron and manganese in paddy soils

Abstract: Iron (Fe) and manganese (Mn) toxicity can be an important limitation to flooded rice cropping. Flooding causes several physical and chemical alterations that affect the dynamics of these elements in the soil environment. The objective of this study was to develop procedures of soil analysis, that enable the assessment of easily reducible Fe and Mn availability and uptake by plants. Surface samples (0 -20 cm) of ten lowland soils from the State of Minas Gerais, Brazil, were used. The experiment consisted of a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It has been suggested that 0.5 N HCl extracts all of the reduced Fe and no oxidized forms (e.g. van Bodegom et al, 2003) and, consequently, that Mehlich-1 extracts all of the reduced plus a given percentage of oxidised Fe (Borges et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that 0.5 N HCl extracts all of the reduced Fe and no oxidized forms (e.g. van Bodegom et al, 2003) and, consequently, that Mehlich-1 extracts all of the reduced plus a given percentage of oxidised Fe (Borges et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Iron toxicity was repeatedly named as a primary limitation to rice cropping in flooded areas around the globe (Borges et al. , 2001; Shimizu et al.…”
Section: Phytotoxins and Plant Responsesmentioning
confidence: 99%
“…Iron toxicity was repeatedly named as a primary limitation to rice cropping in flooded areas around the globe (Borges et al, 2001;Shimizu et al, 2005). High concentrations of both Mn 2+ and Fe 2+ in waterlogged soils were also named as major constraints for growing sensitive wheat cultivars in waterlogging-prone areas of Western Australia and northeastern Victoria wheat belts (Khabaz-Saberi et al, 2010), with two-to ten-fold increase in the shoot Mn and Fe concentrations reported (Khabaz-Saberi et al, 2006).…”
Section: Elemental Toxicitymentioning
confidence: 99%
“…The DTPA (diethylenetriamine-pentaacetic acid) is an effective reagent used for predicting the soil capacity to supply essential nutrients to plants (Mortvedt et al, 1991). It has been used (DTPA-TEA) as extractant to evaluate metal mobility in flooded soils (Borges Jr. et al, 2001). This paper presents the pH measurements and the concentrations of available Zn, Cu, Mn, Pd, and Ni concentrations in a Brazilian Oxisol amended with composted urban solid wastes.…”
Section: Introductionmentioning
confidence: 99%